The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1674-0068/30/cjcp1605113
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4/SnS2 Heterostructure: a Promising Water Splitting Photocatalyst

Abstract: Graphite-like carbon nitride (g-C3N4) based heterostrutures has attracted intensive attention due to their prominent photocatalytic performance. Here, we explore the g-C3N4/SnS2 coupling effect on the electronic structures and optical absorption of the proposed g-C3N4/SnS2 heterostructure through performing extensive hybrid functional calculations. The obtained geometric structure, band structures, band edge positions and optical absorptions clearly reveal that the g-C3N4 monolayer weakly couples to SnS2 sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Based on the single layer fabrication and promising scalable strategy of single layer SnS 2 nanosheets of 3-atom thickness exhibiting above 38% water splitting efficacy under visible light by Yongfu Sun et al Shao-hua Chen et al further investigated the prospects of coupling SnS 2 nanosheets with g-C 3 N 4 to overcome the performance limitations of afore-mentioned research. The results were conformed with the intended improvements of better charge carrier separation and band alignment owing to the weak Vander Walls heterojunction between SnS 2 and g-C 3 N 4 [99]. Another approach using environmentally benign materials and methods was introduced by Rongchen Shen et al, in which the hybridization of Co 2 P nanoparticles formed from phosphorization technique of cobalt metal organic framework and g-C 3 N 4 nanosheets.…”
Section: Graphitic Carbon Nitride and Derivativessupporting
confidence: 58%
“…Based on the single layer fabrication and promising scalable strategy of single layer SnS 2 nanosheets of 3-atom thickness exhibiting above 38% water splitting efficacy under visible light by Yongfu Sun et al Shao-hua Chen et al further investigated the prospects of coupling SnS 2 nanosheets with g-C 3 N 4 to overcome the performance limitations of afore-mentioned research. The results were conformed with the intended improvements of better charge carrier separation and band alignment owing to the weak Vander Walls heterojunction between SnS 2 and g-C 3 N 4 [99]. Another approach using environmentally benign materials and methods was introduced by Rongchen Shen et al, in which the hybridization of Co 2 P nanoparticles formed from phosphorization technique of cobalt metal organic framework and g-C 3 N 4 nanosheets.…”
Section: Graphitic Carbon Nitride and Derivativessupporting
confidence: 58%
“…van der Waals (vdW) heterostructures with the type-II band alignment are effective in improving PCE because the natural spatial separation of VBM and CBM reduces the recombination rate of charge carriers and thus increases the power conversion efficiencies. Both experimental and theoretical , studies have demonstrated that the type-II band alignment in 2D vdW heterostructures, such as CN/CNS, g-C 3 N 4 /NLTO, WS 2 /CdS, MoS 2 /AlN­(GaN), edge-modified PNR, CdS/C 2 N, h-BN/ZrS 2 , and g-C 3 N 4 /ZrS 2 , can not only make the CBM and VBM energy levels meet the needs of redox reactions but also promote the spatial isolation of photogenerated electron–hole pairs and restrain their recombination. Moreover, strong interlayer coupling of charge carriers, long-lived interlayer excitons, and ultrafast charge transfer between layers have been verified in experiments, which will favor the interlayer transfer of the photoexcited carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the formation of the self-induced IEF at the heterojunction interface of two components also accelerated electronic and ionic conduction. According to a higher Fermi level (E f ) of g-C 3 N 4 , [79][80][81] the electrons will transfer from g-C 3 N 4 to SnS 2 until their E f values reach to a balance state. Consequently, at the SnS 2 @g-C 3 N 4 heterointerface, the charge depletion on g-C 3 N 4 and charge accumulation on SnS 2 induce an IEF with an electrical field direction from g-C 3 N 4 to SnS 2.…”
Section: Resultsmentioning
confidence: 99%